Pelaksanaan Uji Coba Program Makan Bergizi Gratis di SMP Negeri 4 Tangerang: Penelitian - Nurul Azzahra; Akbar Dwi Dharmawan; Aras Fikar Mardatilah; Mohamad Ilham Habibi; Virliana Amanda Putri Aryani; Suhardi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The Free Nutritious Meal Program (MBG) is a strategic government policy in an effort to tackle stunting, improve the nutrition of school-age children, and encourage equitable welfare. This study aims to describe the pilot implementation of the MBG program at SMP Negeri 4 Tangerang and evaluate its impact on students. Using a qualitative approach with observation, interview, and documentation techniques. The results show that the program is running well thanks to the cooperation between the school, government, and food providers. The positive impact can be seen from the increased learning focus, student health, and active participation of parents. In addition, the program also helped shape healthy eating habits among students. However, the sustainability of the program still faces challenges related to budget and long-term policies. Therefore, regular evaluation and expansion of program coverage to 3T areas are needed to ensure long-term success.